2010
DOI: 10.1002/elsc.201000074
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methanogenic pathways in anaerobic digesters using stable carbon isotopes

Abstract: In a series of anaerobic batch experiments, the stable carbon isotopes, δ13CCH?4? and δ13CCO?2?, were measured in biogas produced from various sources (maize, cellulose, inoculum) to identify the degradation kinetics and specific methanogenic pathways. Isotopic analysis was performed using a new absorption laser spectrometer in addition to conventional MS. A comparison of the isotopic evolution shows large isotope dynamics for maize and cellulose, indicating a temporal change in degradation pathways and/or a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
5
30
0
Order By: Relevance
“…Generally, microbes preferentially utilize 12 C compounds over 13 C compounds (23). According to the literature, hydrogenotrophic methanogenesis exhibits a significantly larger fractionation factor than that of acetate-dependent methanogenesis due to the ability to select 12 C preferentially during methanogenesis (31,32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, microbes preferentially utilize 12 C compounds over 13 C compounds (23). According to the literature, hydrogenotrophic methanogenesis exhibits a significantly larger fractionation factor than that of acetate-dependent methanogenesis due to the ability to select 12 C preferentially during methanogenesis (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…The relative contribution to methanogenesis via the different metabolic pathways can be determined using the stable isotopic signatures of 13 C/ 12 C. The technique has been used mostly to study biogenic methane formation in anoxic environments and has shown that production of ␦CH 4 from reduction of CO 2 exhibits larger fractionation than that from cleavage of acetate (22,23). In the context of an anaerobic digester, it can be used to study the relative contribution from acetate cleavage and oxidation, with oxidation resulting in a lower 13 CH 4 isotopic signature (␦ 13 CH 4 ) due to differential partitioning of bicarbonate to methane during hydrogenotrophic methanogenesis (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetotrophic and hydrogenotrophic methanogenic bacteria then convert acetic acid and hydrogen, respectively, into a mixture of methane and carbon dioxide. More recent results suggest that the acetate is completely oxidised into CO 2 which in turn is partly reduced to methane (Laukenmann et al 2010). Information on biogas production from main plant biomass components is given in Table 1.…”
Section: General Aspects Of Anaerobic Digestionmentioning
confidence: 99%
“…Commercial IRIS instruments are often designed for atmospheric monitoring and present good accuracy at low and not strongly variable CO 2 concentration [3,7,8]. But there is also a need for carbon isotope monitoring at higher and more variable concentrations, in volcanic [2] or underground [9] environments, as well as for soil [10] and fermentation plants monitoring [11].…”
Section: Introductionmentioning
confidence: 99%